Assessment effectiveness for second language learners: predictors, reliability and discriminant profiles - Figueiredo, Sandra (2020)
The main concerns that enhance the empirical studies in assessment of second language learners is to identify the prevalence of second language deficits, the validity of a new test, and to determine specificities and predictors of speakers’ profiles, among other variables (age, home language formal instruction, exposure to second language, first years of schooling, nationality, parent’s profiles). Hypotheses: different language speakers will perform differently in specific tasks in portuguese language, so age, home language, and first language instruction would be main predictors? Strong discriminant achievements could be identified in percentiles 25 and 75? In this post-doctoral research the main goal is to assess new immigrant students from several Portuguese schools to determine cognitive and linguistic profiles. Through new diagnostic test in second language area will be analyzed distinct verbal behaviors and determined cut-offs. Additionally will be evaluated the difficulty and reliability of each task. Method: the instrument was developed with 15 tasks based on international assessment sources such Alberta, TOEFL, DELNA and WMLSR. There is no knowledge of other validated tools to test portuguese immigrant students. Approximately 110 individuals were assessed, with ages between 7 and 17 years old, speakers of romance, indo-aryan, afro-asiatic, slavic, and mandarin languages, and at this phase we are conducting inferential tests (SPSS) to measure profiles and reliability coefficients. The collection of sample is still ongoing. Findings: in one hand, this paper reports preliminary data gathered from a large-scale district study that is examining language proficiency and cognitive performance of immigrants in Portuguese schools. Different language speakers and age groups, with different amounts of instruction in home language, from basic and high schools, will be analyzed regarding lowest and highest performances in picture-naming (1) and semantic relations tasks (2), particularly focusing the vocabulary decoding skills. Findings demonstrate reliable tasks and different student’s profiles, being crucial over proficiency levels identification. In the other hand, prior findings in this area will be expected to be confirmed such as the influence of age and mother tongue. Part of our hypotheses will be rejected considering the youngest learner’s low scores and the creoles language speakers with deficits in specific vocabulary domain. Particular assumptions of literature in this area will be discussed regarding divergent data observed and new insights. Older learners, with instruction in first language, speakers of slavic, mandarin and romance languages presented more positive results and expected greater cognitive profile in second language specific traits. But, other variables should be considered with further examination and with the conclusion of the empirical study. Also implications of results and test feasibility will be discussed for general educational policies and assessment in second language field.